192k views
2 votes
2x^ - 36 = x using quadratic equation

User Sofiane
by
5.8k points

1 Answer

1 vote

For this case we must solve the following quadratic equation:


2x ^ 2-36 = x\\2x ^ 2-x-36 = 0

Where:


a = 2\\b = -1\\c = -36

The solution is given by:


x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}

Substituting:


x = \frac {- (- 1) \pm \sqrt {(- 1) ^ 2-4 (2) (- 36)}} {2 (2)}\\x = \frac {1 \pm \sqrt {1 + 288}} {4}\\x = \frac {1 \pm \sqrt {289}} {4}\\x = \frac {1 \pm17} {4}

We have two roots:


x_ {1} = \frac {1 + 17} {4} = \frac {18} {4} = \frac {9} {2}\\x_ {2} = \frac {1-17} {4} = \frac {-16} {4} = - 4

Answer:


x_ {1} = \frac {9} {2}\\x_ {2} = - 4

User Kwanzaa
by
6.7k points